From Nobel-winning antiparasitic to antiviral pandemic candidate: A bibliometric analysis of ivermectin’s decades of veterinary and human protection - Alkattan, Abdullah; Albokhadaim, Ibrahim; Almofti, Yassir A.; Elabed, Elayadi; kandeel, Mahmoud (International Journal of Innovative Research and Scientific Studies, 2025)
Ivermectin, a Nobel Prize-winning antiparasitic agent, has gained renewed scientific attention due to its potential antiviral properties, particularly during the COVID-19 pandemic. This study aims to systematically map the global research landscape of ivermectin through a comprehensive bibliometric analysis. A total of 3,723 articles indexed in Scopus from 1980 to April 2025 were analyzed using bibliometric tools including VOSviewer and Bibliometrix. The study evaluated research productivity, citation patterns, geographic distribution, collaboration networks, and thematic evolution. Keyword co-occurrence and overlay visualization were applied to map classical and emerging trends. The annual publication rate increased at an average of 4.89%, with a sharp rise between 2020 and 2022 during the COVID-19 pandemic. Articles had an average of 25.06 citations and involved 5.71 co-authors per document. The United States led in publication output, followed by Brazil and China, with Mahidol University being the most productive institution. Six thematic clusters were identified: veterinary parasitology and resistance; neglected tropical diseases; toxicity and resistance mechanisms; antiviral repurposing (COVID-19); dermatological applications; and scabies treatment. Emerging areas of focus include nanodelivery systems and SARS-CoV-2-related studies. Ivermectin's research trajectory reflects its evolving role beyond antiparasitic use, especially during global health crises. The pandemic significantly accelerated its repositioning as a potential antiviral agent, although this trend varies across regions and institutions. This study highlights ivermectin’s expanding therapeutic landscape and underscores the need for balanced global collaboration. Future research should focus on the development of novel delivery technologies and robust clinical trials to substantiate its antiviral efficacy as well as testing its potential broad-spectrum antiviral activity.